Dioxygen splitting at room temperature over distant binuclear transition metal centers in zeolites for direct oxidation of methane to methanol - Mlekodaj, Kinga; Lemishka, Mariia; Sklenak, Stepan; Dedecek, Jiri; Tabor, Edyta (Royal Society of Chemistry, 2021)
Here we demonstrate for the first time the splitting of dioxygen at RT over distant binuclear transition metal (M = Ni, Mn, and Co) centers stabilized in ferrierite zeolite. Cleaved dioxygen directly oxidized methane to methanol, which can be released without the aid of an effluent to the gas phase at RT.
Štěpení kyslíku při pokojové teplotě na vzdálených dvouatomových centrech přechodových kovů v zeolitech pro přímou oxidaci metanu na metanol
Keywords: zeolites; oxidation of methane; transition metals; dioxygens; room temperature; zeolity; oxidace metanu; přechodové kovy; kyslík; pokojová teplota